Psicologia Analítica no Brasil Contribuições para a sua história - Motta, Arnaldo Alves da (2005)
Abstract The purpose of this work is to study the formation of analytical psychology in Brazil. To this end, a social approach in the history of psychology was used seeking to place people and facts in a general context once history is inserted in a certain time and place. Three figures considered pioneers in this field in the country were identified Nise da Silveira, Pethö Sándor and Leon Bonaventure whose personal and professional paths are addressed. At the same time, also noted, are the possible related broader events and situations that may be related to their being responsible for their role as pioneers. In mapping the contributions made by these professionals in the field of analytical psychology, one perceives the development of a creative work not limited to the dissemination of Carl Gustav Jung s concepts, but to the proposition of their own methods and techniques. Furthermore, particularly in the work of the two first pioneers researched, one observes the collaboration toward the birth of a Brazilian analytical psychology.